Diabetes-related intestinal region-specific thickening of ganglionic basement membrane and regionally decreased matrix metalloproteinase 9 expression in myenteric ganglia - Bódi, Nikolett (World J Diabetes, 2021)
BACKGROUND: The importance of the neuronal microenvironment has been recently highlighted in gut region-specific diabetic enteric neuropathy. Regionally distinct thickening of endothelial basement membrane (BM) of intestinal capillaries supplying the myenteric ganglia coincide with neuronal damage in different intestinal segments. Accelerated synthesis of matrix molecules and reduced degradation of matrix components may also contribute to the imbalance of extracellular matrix dynamics resulting in BM thickening. Among the matrix degrading proteinases, matrix metalloproteinase 9 (MMP9) and its tissue inhibitor (TIMP1) are essential in regulating extracellular matrix remodelling. AIM: To evaluate the intestinal segment-specific effects of diabetes and insulin replacement on ganglionic BM thickness, MMP9 and TIMP1 expression. METHODS: Ten weeks after the onset of hyperglycaemia gut segments were taken from the duodenum and ileum of streptozotocin-induced diabetic, insulin-treated diabetic and sex- and age-matched control rats. The thickness of BM surrounding myenteric ganglia was measured by electron microscopic morphometry. Whole-mount preparations of myenteric plexus were prepared from the different gut regions for MMP9/TIMP1 double-labelling fluorescent immunohistochemistry. Post-embedding immunogold electron microscopy was applied on ultrathin sections to evaluate the MMP9 and TIMP1 expression in myenteric ganglia and their microenvironment from different gut segments and conditions. The MMP9 and TIMP1 messenger ribonucleic acid (mRNA) level was measured by quantitative polymerase chain reaction. RESULTS: Ten weeks after the onset of hyperglycaemia, the ganglionic BM was significantly thickened in the diabetic ileum, while it remained intact in the duodenum. The immediate insulin treatment prevented the diabetes-related thickening of the BM surrounding the ileal myenteric ganglia. Quantification of particle density showed an increasing tendency for MMP9 and a decreasing tendency for TIMP1 from the proximal to the distal small intestine under control conditions. In the diabetic ileum, the number of MMP9-indicating gold particles decreased in myenteric ganglia, endothelial cells of capillaries and intestinal smooth muscle cells, however, it remained unchanged in all duodenal compartments. The MMP9/TIMP1 ratio was also decreased in ileal ganglia only. However, a marked segment-specific induction was revealed in MMP9 and TIMP1 at the mRNA levels. CONCLUSION: These findings support that the regional decrease in MMP9 expression in myenteric ganglia and their microenvironment may contribute to extracellular matrix accumulation, resulting in a region-specific thickening of ganglionic BM.